Comparative evaluation of the skeletal and dentoalveolar effects of Thurow and activator appliances in patients with Class II malocclusion - maryam omidkhod; mahboobe dehghani; fatemeh rezaeian; mehrnaz fakharian (Mashhad University of Medical Sciences, 2018)
Introduction: Class II malocclusion is an evolutionary problem caused by deviated maxillary and mandibular growth. Various types of orthopedic devices have been introduced to correct this malformation. The aim of the present study was to evaluate and compare the skeletal and dental effects of activator and Thurow appliances in patients with Class II malocclusion. Method and Materials: This retrospective study was conducted on 26 patients with Class II malocclusion. The patients were within the age range of 9-12 years before the growth spurt and at the time of the treatment initiation and had Class II Division 1 malocclusion, Class II molar relationship, ANB of > 4, and overjet of > 5. They were under treatment for one year. The participants were divided into two groups of Thurow and Activator, based on the device used. The tracing of the lateral cephalometric radiographs was performed at the beginning of the treatment (T1) and 12 months after that (T2). Finally, the mean scores of cephalometric variables were compared between the two groups and between the two treatment stages (i.e., T1 and T2).Using independent T and Man-Whitney u test. Results: In the activator group, the variables of ANB, N-A-Pog, U1-L1, L1-MP, U1-NA, L1-NB, overjet, Co-A, and Co-GN were significantly different between the pre- and pot-intervention stages. Furthermore, regarding the Thurow group, a significant difference was observed between the two research stages in terms of SNA, ANB, N-A-Pog, U1-L1, U1-NA, overjet, overbite, and N-perpendicular A. Between the Thurow and activator devices, only L1-MP showed a statistically significant difference after the treatment. Conclusion: As the findings indicated, Thurow device was only suitable for preventing maxillary growth and exerted no significant effect on the mandible. On the other hand, functional class II device (i.e., activator) was effective for stimulating the growth of the mandible and did not inhibit the maxillary growth.